The effects of vortex gate design on mechanical strength of thin section casting of LM 25 (Al---7Si-0.3Mg) aluminum casting alloy - Subhi, Zaid Ali (2012)
Aluminum alloy castings are being used progressively more in safety-critical applications in the automotive and aerospace industries. During the production of aluminum ingots and castings, the surface oxide on the liquid is folded in to produce crack-like defects (bifilms), porosities that are extremely thin and tiny or big, but can be extremely extensive, and so constitute seriously detrimental defects. To produce castings of sufficient quality, it is, therefore, important to understand the mechanisms of the formation of defects in aluminum melt flow through the gating system. Gating system design is an essential element in casting process which affects significantly the molten metal flow behavior, heat transfer and solidification of the melt. The good quality casting product could be achieved by using an optimum gating design. This study has employed Vortex gate design of LM25 (Al—7Si-0.3Mg) thin section casting to determine the effect of Vortex and Conventional gate design on mechanical properties and porosity distribution pattern. Numerical simulation by ADESTEFAN v.10 package was used to identify the molten metal flow behavior in the mold cavity which is physically could not be detected by unaided eye. The X-Ray Radiography test used to examine in general the distribution of defects in thin casted part. 3-Point bending test was applied to measure the flexural strength of the casted alloy material. The scattering of flexural strength has been quantified by Weibull statistics approach. The microstructure inspection was observed using both, the optical microscope micrographs and scanning electron machine (SEM) tests. Numerical simulation results showed a smooth and non turbulent flow of the Vortex gate design. The liquid metal in vortex entering the mould cavity is helped by gravity for a good free surface condition during filling, reducing the danger of entrapment of any free surface film. Furthermore, experimental results showed that casting product with vortex gate leads to excellent improvement of average flexural strength and reduction of porosity and cracks defects relying on the feature of swirled flow inside the vortex gate. The ‘virtual’ experiment using a computational modeling package and the ‘physical’ experiment were found to be in reasonable agreement. 377$ 3(53867$.$$1781.8781$0,1$+